Peningkatan Pengetahuan, Sikap, dan Keterampilan Orang Tua tentang Gizi Anak - Santun Setiawati; Titi Sulastri; Agus Citra Dermawan; Ratna Ningsih (Jurnal Keperawatan, 2023)
Introduction: malnutrition is still a problem in Indonesia. The general objective of this study was to determine the effect of health education media (video and print media) on parents' knowledge, attitudes and skills regarding nutrition before and after the intervention. Methods: quasi-experimental research design, the sample is parents who have preschool and preschool age children with a total of 60 respondents (30 people in the intervention group and 30 people in the control group); independent variables: parental characteristics and child characteristics, and dependent variable: parental knowledge, parental attitudes and parental skills; The instruments were in the form of demographic data and questionnaires about knowledge, attitudes, and skills regarding nutrition in the elderly, analysis tests using univariate analysis (frequency distribution) and bivariate (t dependent and independent tests). The results of the study showed that there was an increase in parents' knowledge, attitudes and skills regarding nutrition in children. Conclusion: health education media (video and print media) can increase parents' knowledge, attitudes, and skills about nutrition in children, although not significantly. Implication: health education media (video and print media) can be used alternative to increase knowledge, attitudes, and skills about nutrition in children.